Cytotoxic and genotoxic assessments of 2,4-dichlorophenoxyacetic acid (2,4-D) in in vitro mammalian cells - Laborde, Milagros Rosa Raquel (2020)
A combined approach employing alkaline single cell gel electrophoresis (SCGE) and cytokinesis-blocked micronucleus (MNs) cytome bioassays was adopted to assess the deleterious properties of the auxinic 2,4-dichlorophenoxyacetic acid (2,4-D) and its microparticulated low volatility product Dedalo Elite (30% a.i.) on Chinese hamster ovary (CHO-K1) cells. Cytotoxicity was estimated by neutral red uptake (NRU), succinic dehydrogenase activity (MTT) and apoptosis assessment. Both compounds were assayed at 0.1–10 μg/ml concentration range. Whereas exposed CHO-K1 cells revealed a statistically significant enhancement of MNs when 10 μg 2,4-D/ml was assayed, MNs were only achieved in cells treated with 2 μg Dedalo Elite/ml. A diminution in the nuclear division index was only achieved after exposure to Dedalo Elite within the 1–10 μg/ml concentration range. Whereas increased genetic damage index was achieved when 6 and 10 μg 2,4-D/ml were assayed, GDI induction was observed in treatments employing 4 μg Dedalo Elite/ml. Both compounds induced cytotoxicity by inhibition of both lysosomal and MTT activities by enhancing the frequencies of early and late apoptotic cells. Our results not only indicate the genotoxic and cytotoxic potential of 2,4-D and its microparticulated marketplace formulation, but also highlight the risk of these agrochemicals present towards the biota and human health.